2016
DOI: 10.1213/ane.0000000000001042
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Pain Management in Children of Hispanic Origin

Abstract: Background It has been established that pain is frequently undertreated in children following outpatient surgery. Very few studies, however, have investigated this phenomenon in ethnically diverse populations. Methods This study included 105 families of children age 2–15 years of Hispanic origin and low income undergoing outpatient tonsillectomy and adenoidectomy surgery. Participating parents completed baseline and demographic packets. Recorded postoperative pain ratings and administration of analgesics at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 26 publications
(33 reference statements)
0
32
2
Order By: Relevance
“…Two studies examined the relationship between parent ethnicity and culture and at‐home administration of analgesia after surgery. In Rosales and colleagues’ study, many Latino parents demonstrated fears about pain medication which predicted lower doses of postoperative analgesics at home; Brown and others showed that Latino children had poor pain control at home after surgery while there was no relationship between Latino parents’ acculturation status and administration of analgesia to their children after day surgery . Another study focused on care in the PACU, and noted that after routine tonsillectomy and adenoidectomy Black children reported higher postoperative pain and required more pain medications, suggesting inter‐individual and inter‐racial variability in opioid requirements .…”
Section: Discussionmentioning
confidence: 99%
“…Two studies examined the relationship between parent ethnicity and culture and at‐home administration of analgesia after surgery. In Rosales and colleagues’ study, many Latino parents demonstrated fears about pain medication which predicted lower doses of postoperative analgesics at home; Brown and others showed that Latino children had poor pain control at home after surgery while there was no relationship between Latino parents’ acculturation status and administration of analgesia to their children after day surgery . Another study focused on care in the PACU, and noted that after routine tonsillectomy and adenoidectomy Black children reported higher postoperative pain and required more pain medications, suggesting inter‐individual and inter‐racial variability in opioid requirements .…”
Section: Discussionmentioning
confidence: 99%
“…Given the lack of consensus standards for analgesia after pediatric outpatient surgery, suboptimal provision of analgesia 2,9 and growing fears about opioids, there is an urgent need for evidence to guide outpatient analgesic choices for children at discharge. We sought to evaluate whether oral morphine was su perior to ibuprofen for relieving children's pain at home, after minor outpatient orthopedic surgery.…”
mentioning
confidence: 99%
“…The difference in children's subjective pain in our study and that in other foreign studies may be explained by the following reasons. First, the children's expression of pain or caregivers’ interpretation of children's pain responses has been reported to vary according to their culture (Brown et al, ; Kristjansdottir et al, ; Liao et al, ). Liao et al () argued that Asians tend to less likely to express their pain symptoms to others and enduring pain, which may lead to inaccurate examination and interpretation of children's pain.…”
Section: Discussionmentioning
confidence: 99%